Slow and stopped-light lasing in active plasmonic metamaterials - K. L. Tsakmakidis; Hess, O. (International Conference on Transparent Optical Networks, 2012)
We outline recent advances in active gain-enhanced plasmonic metamaterials revealing and elucidating the inherent complex interplay of light, surface plasmon polaritons and gain materials to allow a compensation of dissipative losses in negative-refractive-index optical metamaterials and to achieve net steady-state amplification and nanoscopic lasing over a broad but ultrathin area. On the basis of a fully 3-dimensional Maxwell-Bloch Langevin approach we then demonstrate that in a suitably designed gain-enhanced plasmonic/ metamaterial heterostructure light pulses can be completely stopped at well-accessed complex-frequency zero-group-velocity points leading to thresholdless nanolasers that beat the diffraction limit via a novel, stopped-light mode-locking mechanism. © 2012 IEEE.